Pengaruh Curah Hujan dan Hari Hujan Terhadap Produksi Tanaman Karet (Hevea brasiliensis Muell-Arg.) Umur 6, 10 dan 14 Tahun pada PT. Bridgestone Sumatera Rubber Estate Dolok Merangir - Margareth Thacher Manurung hidayat; Irsal Irsal; Haryati Haryati (Universitas Sumatera Utara, 2015)
One of determining factors of water supply for rubber plants are rain fall and rain day. Rain fall andrain day are factor of climates that often change as impact by climate changes. Climate changes cannegatively or positively effect rubber plantation production. This research was done inPT. Bridgestone Sumatra Rubber Estate plantations Dolok Merangir, Kecamatan Dolok BatuNanggar, Kabupaten Simalungun, North Sumatra Province, from February to Maret 2014. Thisresearch used to studied about influence of rain fall and rain day toward rubber plantationproduction aged 6, 10, 14 years in plantation. This reasearch used primary data that used foranalysis consists of latex production; rain fall data and rain day monthly in 2010-2012. Theanalysis method was double linier regression analysis and correlation analysis. Model analysistested by classic asumption test consists of normality test, heteroskedasticity test, multicollinearity,and autocorelations test by using statistic software SPSS.v.17 for windows. The regression analysisshows that rain fall and rain day variables not significant with alpha 5% (Sig > α 0,05) toincreased latex production of rubber plants aged 6, 10 and 14 years. The result from classicalassumption tests that used for seeing the feasibility of multiple regression equation concluded thatthe rubber plants aged 6, 10, and 14 years are qualified. The correlation result of rain fall and rainday with two-tailed analysis using significant level 1% is weak against the latex production ofrubber plants aged 6, 10 and 14 years.The largest correlation value contained between rain fall andrain day are 0,933 each with significant level 0,000 (Sig <α 0,01).Keywords: latex production, rain day, rain fall.